Successful Experience of Laparoscopic Pancreaticoduodenectomy and Digestive Tract Reconstruction With Minimized Complications Rate by 14 Case Reports. Issue 17 (April 2016) - Fan, Yong; Zhao, Yanhui; Pang, Lan; Kang, Yingxing; Kang, Boxiong; Liu, Yongyong; Fu, Jie; Xia, Bowei; Wang, Chen; Zhang, Youcheng
Abstract : Abstract: Laparoscopic pancreatic surgery is one of the most sophisticated and advanced applications of laparoscopy in the current surgical practice. The adoption of laparoscopic pancreaticoduodenectomy (LPD) has been relatively slow due to the technical challenges. The aim of this study is to review and characterize our successful LPD experiences in patients with distal bile duct carcinoma, periampullary adenocarcinoma, pancreas head cancer, and duodenal cancer and evaluate the clinical outcomes of LPD for its potential in oncologic surgery applications. We retrospectively analyzed the clinical data from 14 patients who underwent LPD from August 2013 to February 2015 in our institute. We presented our LPD experience with no cases converted to open surgery in all 14 cases, which included 10 cases of laparoscopic digestive tract reconstruction and 4 cases of open digestive tract reconstructions. There were no deaths during the perioperative period and no case of gastric emptying disorder or postoperative bleeding. The other clinical indexes were comparable to or better than open surgery. Based on our experience, LPD could be potentially safe and feasible for the treatment of early pancreas head cancer, distal bile duct carcinoma, periampullary adenocarcinoma, and duodenal cancer. The master of LPD procedure requires technical expertise but it can be accomplished with a short learning curve.